2023
DOI: 10.7759/cureus.37360
|View full text |Cite
|
Sign up to set email alerts
|

Tietze Syndrome as a Cause of Chest Pain in the Post-COVID-19 Period

Abstract: Tietze syndrome is a rare disease. It is mainly characterized by chest pain caused by a unilateral and monoarticular lesion of the second-fifth costal joints. Tietze syndrome is one of the potential complications in the post-COVID-19 period. It is one of the differential diagnoses for non-ischemic chest pain. With early diagnosis and appropriate treatment, this syndrome is easily manageable. The authors present a case of a 38-year-old male who had been diagnosed with Tietze syndrome in the post-coronavirus dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The etiology and mechanism remain largely unknown, although hypotheses suggest microtrauma from repetitive coughing and vomiting. Notably, recent research has shown Tietze syndrome in some patients after COVID-19 infection [3]. Differential diagnosis primarily includes costochondritis; despite its benign nature, Tietze syndrome can cause significant discomfort and mimic more serious conditions such as acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology and mechanism remain largely unknown, although hypotheses suggest microtrauma from repetitive coughing and vomiting. Notably, recent research has shown Tietze syndrome in some patients after COVID-19 infection [3]. Differential diagnosis primarily includes costochondritis; despite its benign nature, Tietze syndrome can cause significant discomfort and mimic more serious conditions such as acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%